2021
DOI: 10.3389/fpls.2021.760520
|View full text |Cite
|
Sign up to set email alerts
|

SEVEN IN ABSENTIA Ubiquitin Ligases Positively Regulate Defense Against Verticillium dahliae in Gossypium hirsutum

Abstract: Ubiquitination is a post-translational regulatory mechanism that controls a variety of biological processes in plants. The E3 ligases confer specificity by recognizing target proteins for ubiquitination. Here, we identified SEVEN IN ABSENTIA (SINA) ubiquitin ligases, which belong to the RING-type E3 ligase family, in upland cotton (Gossypium hirsutum). Twenty-four GhSINAs were characterized, and the expression levels of GhSINA7, GhSINA8, and GhSINA9 were upregulated at 24 h after inoculation with Verticillium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Chinese Spring, including five sequences from subgenome A, five sequences from subgenome B and five sequences from subgenome D (Supporting Information: Table ). Each protein sequence contained a conserved RING‐finger domain at the N‐terminus and a SINA domain with approximately 200 conserved amino acid residues at the C‐terminus (Figure 1a; Ren et al, 2021). A phylogenetic tree was constructed using the protein sequences of SINAs from Arabidopsis and wheat, and all the SINAs were divided into two groups, with nine TaSINAs and three Arabidopsis SINAs in Group I, and six TaSINAs and two Arabidopsis SINAs in Group II (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinese Spring, including five sequences from subgenome A, five sequences from subgenome B and five sequences from subgenome D (Supporting Information: Table ). Each protein sequence contained a conserved RING‐finger domain at the N‐terminus and a SINA domain with approximately 200 conserved amino acid residues at the C‐terminus (Figure 1a; Ren et al, 2021). A phylogenetic tree was constructed using the protein sequences of SINAs from Arabidopsis and wheat, and all the SINAs were divided into two groups, with nine TaSINAs and three Arabidopsis SINAs in Group I, and six TaSINAs and two Arabidopsis SINAs in Group II (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…All the high‐confidence protein sequences in the wheat genome (IWGSC RefSeq v2.1) were applied in a Hidden Markov Model searching using the HMM profile from the PFAM platform to identify TaSINAs (Finn et al, 2006; Letunic et al, 2009; Zhu et al, 2021). Any protein containing a conserved RING‐finger domain at the N‐terminus and a SINA domain with approximately 200 conserved amino acid residues at the C‐terminus was considered a TaSINA (Figure 1a; Ren et al, 2021). Additionally, the full‐length SINA protein sequences from Arabidopsis and wheat were used for the construction of a phylogenetic tree using MEGA11 software (Tamura et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only one SUMO‐E3 ligase, SIZ1, has been shown to mediate PHR1 activity in response to Pi starvation (Miura et al, 2005), and the E3 ligase NLA has been shown to mediate PHR1 stability in Arabidopsis (Park et al, 2023). The SINA E3 ligases are member of the RING E3 ligase family, which is widely involved in regulating plant growth and development and stress responses (Xie et al, 2002; Ning et al, 2011; Bao et al, 2014; Miao et al, 2016; Fan et al, 2017; Yang et al, 2017; Zhang et al, 2019; Lee et al, 2021; Ren et al, 2021). In apple, MdSINA2 negatively regulates abscisic acid (ABA) signaling, and MdSINA3 inhibits jasmonic acid (JA)‐induced leaf senescence (Li et al, 2020; An et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As an important member of ubiquitin-proteasome pathway, SINA E3 ligase has been proved to have extensive and rich regulatory effects in many plants, including the growth and development of plant tissues (Xie et al, 2002; Park et al, 2007; Park et al, 2010; Wang et al, 2018), secondary metabolism (Welsch et al, 2007), symbiotic nitrogen fixation (Den et al, 2008), autophagy and drought stress responses (Ning et al, 2011; Bao et al, 2014; Qi et al, 2017), cold stress responses (Fan et al, 2017), plant immunity (Miao et al, 2016; Wang et al, 2018; Ren et al, 2021) and so on. Plant SINA proteins have been studied to be located in the nucleus or cytoplasm in the past (Wang et al, 2018; Li et al, 2020; Xia et al, 2020; Ren et al, 2021). In this study, we identified a significantly drought-induced gene SsSINA1a located in the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%